1979
DOI: 10.1139/z79-292
|View full text |Cite
|
Sign up to set email alerts
|

Social and reproductive behavior of crabeater seals (Lobodon carcinophagus) during the austral spring

Abstract: The social and reproductive behaviors of crabeater seals (Lobodon carcinophagus) were studied from September through November, during 1975, 1976 and 1977. Seals were immobilized, or controlled with a canvas bag over the head, then tagged and measured. Behavioral observations were recorded on all seals encountered.Crabeater seals were classified into three groups: (1) family groups (2) mated pairs, and (3) fast ice concentrations. Family groups consisted of an adult female, her pup, and an adult male. After wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(67 citation statements)
references
References 8 publications
1
66
0
Order By: Relevance
“…Siniff et al (1979) observed that breeding crabeater seals tended to seek out larger floes than did non-breeding seals, although their statistical analysis indicated no significant association between breeding status and floe size. Our finding of a significant association between the presence of breeding seals and the proportion of ice as floes < 20 m suggests that, rather than seeking out large floes, breeding seals may avoid floes < 20 m in size or areas with a high proportion of floes < 20 m. Crabeater seals presumably stay on the same floe throughout the weaning period, given the poor mobility of pups and the accumulation of faeces nearby.…”
Section: Discussionmentioning
confidence: 90%
“…Siniff et al (1979) observed that breeding crabeater seals tended to seek out larger floes than did non-breeding seals, although their statistical analysis indicated no significant association between breeding status and floe size. Our finding of a significant association between the presence of breeding seals and the proportion of ice as floes < 20 m suggests that, rather than seeking out large floes, breeding seals may avoid floes < 20 m in size or areas with a high proportion of floes < 20 m. Crabeater seals presumably stay on the same floe throughout the weaning period, given the poor mobility of pups and the accumulation of faeces nearby.…”
Section: Discussionmentioning
confidence: 90%
“…Siniff et al 1979, Shaughnessy & Kerry 1989. It is not known if female crabeater seals also produce underwater vocalizations and if the occurrence of the high moan could possibly be attributed to females advertising their sexual receptivity.…”
Section: Mating Systemmentioning
confidence: 99%
“…Moreover, for pupping, crabeater seal females select ice floes based on floe size and physical characteristics (i.e. surface relief; Siniff et al 1979) which offer protection from predation by leopard seals and orcas. Changes affecting the availability and duration of availability of such sea-ice types might also directly affect crabeater seal populations, e.g.…”
Section: Implications Of a Changing Environment For Antarctic Pinnipedsmentioning
confidence: 99%
“…Scat and stomach contents analysis suggests that Adelie penguins Pygoscelis adeliae are eaten throughout the year, but are also the main prey item in the Prydz Bay region during the austral summer (Rogers & Bryden 1995, Hall-Aspland & Rogers 2004. Crabeater seals Lobodon carcinophagus become important in the diet between November and February when newly weaned pups are available as easy prey targets (Siniff & Bengtson 1977, Siniff et al 1979, Bengtson 1982, Siniff & Stone 1985. Krill and fish are preyed on throughout the summer from September to March whereas Antarctic silverfish Pleuragramma antarcticum predominated during winter (Green & Williams 1986).…”
Section: Introductionmentioning
confidence: 99%